2013
DOI: 10.1111/1365-2664.12176
|View full text |Cite
|
Sign up to set email alerts
|

Living in risky landscapes: delineating management units in multithreat environments for effective species conservation

Abstract: Summary1. Managing threatened species to reduce their extinction risk is a widely used, yet challenging, means of halting biodiversity loss. Species show complex spatial patterns of extinction risk, due to spatial variation in both threats and vulnerability across their ranges. Conservation practitioners, however, rarely consider this spatial variation and routinely apply uniform conservation schemes, either throughout the species' ranges, or following administrative borders that do not match ecological bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Therefore, managing the AMUs separately assumes that these units equate to GMUs, thus representing more or less disconnected (i.e., closed or genetically separated) populations that experience limited reproductive exchange of individuals with other populations (Moritz 1994). However, several recent studies have shown that if this implicit assumption is violated in wildlife management, actions in one management unit (MU) can substantially influence management effectiveness in neighboring units (Hemami et al 2005;Robinson et al 2008;Olea and Mateo-Tomás 2014;Stillfried et al 2017). In such cases, management would need to be extended towards a larger spatial scale that includes multiple MUs and considers the degree of connectivity among them (e.g., Robinson et al 2008;Wäber et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, managing the AMUs separately assumes that these units equate to GMUs, thus representing more or less disconnected (i.e., closed or genetically separated) populations that experience limited reproductive exchange of individuals with other populations (Moritz 1994). However, several recent studies have shown that if this implicit assumption is violated in wildlife management, actions in one management unit (MU) can substantially influence management effectiveness in neighboring units (Hemami et al 2005;Robinson et al 2008;Olea and Mateo-Tomás 2014;Stillfried et al 2017). In such cases, management would need to be extended towards a larger spatial scale that includes multiple MUs and considers the degree of connectivity among them (e.g., Robinson et al 2008;Wäber et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the current practice of applying uniform management and conservation schemes over large spatial scales often ignores the fact that the types and intensities of threats may vary in space and time across the range of a single species, and sometimes even among adjacent populations (e.g., Cowlishaw et al 2009;Olea and Mateo-Tomás 2014). Therefore, assessing spatial variation in threats and management practices across local populations is crucial for successful species conservation, yet this issue has so far received only rudimentary attention from scientists and conservation practitioners (Olea and MateoTomás 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively high collision fatality rates have been recorded at several large wind farms in locations indicating that turbines pose a risk, especially to large raptors and other soaring birds (Marques et al 2014). The Griffon vulture ( Gyps fulvus ) is one of the raptor species frequently killed by collision with wind turbines in southern Spain (Barrios and Rodríguez 2004; De Lucas et al 2008, 2012; Olea and Mateo‐Tomás 2014). For instance, Carrete et al (2012) found 342 dead Griffon vultures during a 10‐year period (Jan 1998–Mar 2008) in an area of 34 wind farms with 799 turbines in the province of Cádiz, southern Spain.…”
mentioning
confidence: 99%